Speech Acts and Educational Management Orientation: An Illocutionary Analysis of President Prabowo Subianto’s Address at the 2025 MPR RI Annual Session - Ummu Kalsum A. Hamzah; Muh Hasbi; Aslan Abidin (Al-Qalam Institue, 2026)
This study aims to analyze the types and communicative functions of illocutionary acts employed in President Prabowo Subianto’s address delivered at the 2025 Annual Session of the People’s Consultative Assembly of the Republic of Indonesia (MPR RI) and to examine their implications for national education management. Using a qualitative descriptive approach grounded in Searle’s Speech Act Theory, the data were obtained from the official transcript of the presidential address and analyzed through systematic classification and interpretative analysis. The findings reveal that representative and directive illocutionary acts dominate the speech, indicating the President’s efforts to assert national conditions, legitimize strategic policy directions, and encourage collective participation, including in the education sector. Commissive acts reflect governmental responsibility and long-term commitment to educational reform and human resource development, while expressive acts function to reinforce moral values, ideological orientation, and emotional engagement with stakeholders. These results suggest that illocutionary acts serve as strategic tools in political communication and leadership discourse. The study implies that understanding speech acts in presidential discourse is essential for education managers and policymakers, as such discourse shapes policy orientation, institutional governance, and the implementation of national education management strategies